Association of serum uric acid and serum lipid profile in pre- eclampsia- A hospital based case-control study - Rizal, Shikha; Joshi, Bishal Raj; Dhakal, Amita; Sagtani, Reshu Agrawal (Birat Journal of Health Sciences, 2020)
Introduction: Pre-eclampsia, one of the most common medical complication in pregnancy results in considerable maternal and fetal morbidity and mortality. Endothelial dysfunction is a central feature of pre-eclampsia. Elevated serum uric acid level may serve as a marker for early diagnosis of the disease as well as a surrogate for clinical severity of the condition. High serum values of triglycerides, total cholesterol, low- density lipoprotein and and low levels of high density lipoprotein are all significantly related to risk developing preeclampsia. Objective: To find out the association between serum uric acid levels and lipid profile in pre-eclamptic women and compare it with the normal pregnant women. Methodology: A case control study was conducted among 180 pregnant women (90 cases of pre-eclamptic women and 90 cases of age matched normal pregnant women) between 21-35 years who were admitted in the Gynaecology and Obstetrics ward of Nobel Medical College and Teaching Hospital, Biratnagar. Blood pressure was measured. Serum from all the patients were analyzed for the following biochemical parameters: serum uric acid, triglyceride, total cholesterol, LDL-C and HDL- C. The data were collected and entered in MS-Excel and analyzed using Statistical Package for Social Sciences (SPSS) ver. 16 software. Results: Mean serum uric acid of pre-eclamptic women was higher than those of normal pregnant women which was found to be statistically significant with p value <0.001. Among the lipid parameters, serum triglyceride and total cholesterol was significantly higher in pre-eclamptic women whereas high density lipoprotein was significantly lower in pre-eclamptic. Also there was a positive co-relation between triglyceride and blood pressure and a negative co-relation between HDL-C in preeclamptic women. Conclusion: Development of simple and inexpensive methods to predict and prevent pre-eclampsia in early stage is very important. Thus, our study concludes the utility of measurement of serum uric acid and lipid profile for screening patients at risk of developing pre-eclampsia.